Perancangan dan Implementasi Aplikasi Marketplace Barang Bekas “LOAK.IN” Berbasis Web Menggunakan Framework Laravel - Much Nur Syams Simaja; Rizal Amri Khoirul Hakim Ritonga; Amira Salsabila; Muhammad Farraz Fatih; Jati Nur Shiddiq; Dhafa Aulia; Ika Yusnita Sari (CV. Shofanah Media Berkah, 2025)
Currently, the trade in used goods is still largely conducted through unstructured social media and instant messaging groups, resulting in problems in searching for goods, managing seller data, and moderating content. This study aims to design and implement a web-based used goods marketplace application called LOAK.IN as a solution to organize used goods buying and selling activities in a more structured manner. This solution is realized through the development of a web application using the Laravel framework with a Model-View-Controller (MVC) architecture. The research method used is the Waterfall software development model, which includes the stages of analysis, design, implementation, and testing. Functional testing was conducted using the black-box testing method for all system requirements. The results show that all main functionality of the application runs according to the specified specifications and the system operates stably, so LOAK.IN can be used as a functional solution to support more organized used goods transactions.